Orthopaedic Surgery Faculty: An Evaluation of Gender and Racial Diversity Compared with Other Specialties. Issue 3 (July 2020) - Shah, Kalpit N.; Ruddell, Jack H.; Scott, Brandon; Reid, Daniel B.C.; Sobel, Andrew D.; Katarincic, Julia A.; Akelman, Edward
Abstract : Background: The American Academy of Orthopaedic Surgeons has adopted the strategic goal of evolving its culture and governance to become more strategic, innovative, and diverse. Given the charge to increase diversity, a focus on assessing and increasing diversity at the faculty level may help this cause. However, an analysis of gender and racial diversity among orthopaedic faculty has not been performed. The purpose of this study was to evaluate faculty appointments for underrepresented minority (URM) and female orthopaedic surgeons. We also aim to draw comparisons between orthopaedic surgery and other specialties. Methods: Data on gender, race, and faculty rank (clinical instructor, assistant professor, associate professor, and professor) of academic faculty for 18 specialties from 1997 to 2017 were obtained from the Association of American Medical Colleges (AAMC) Faculty Roster. Assistant professors were designated as junior faculty, whereas associate professor and professor were considered senior faculty. URMs were defined using the AAMC definition—groups having lower representation than in the general population. Regression analysis was used to evaluate and compare the change over time and to compare the change across different specialties. Results: Over the 20-year study period, the number of female faculty increased (8.8% pts) but represents a lower proportion than other specialties (13.9% pts) (p = 0.029). Female orthopaedic senior faculty grew slower (7.3% pts) than other specialties (14.7% pts) (p < 0.001). There was no difference in the growth of URM faculty positions (2.0% pts) compared with all other specialties (2.4% pts) (p = 0.165). The proportion of orthopaedic URM senior faculty increased less (0.5% pts) than other specialties (2.5% pts) (p < 0.001), whereas more orthopaedic URM junior faculty were added than other specialties (2.2% pts) (p = 0.012). Conclusions: Although orthopaedic surgery has increased the representation of female and URM faculty members, it continues to lag behind other specialties. In addition, fewer female and URM orthopaedic faculty members obtained senior faculty status than other specialties. To address the differences seen in faculty diversity, a concerted effort should be made to recruit and promote more diverse faculty, given similar qualifications and capabilities. Level of Evidence: Prognostic Level IV .